Plasma technology in fashion and textiles - Zille, Andrea (2019)
In recent years, plasma technology has assumed a great importance among all available textile surface modification processes. It is a dry, environmentally and worker-friendly method to achieve surface alteration without modifying the bulk properties of different materials. The most used plasma classification divides plasmas in two categories: thermal plasma, when species are in thermal equilibrium, and cold plasma, when species are not in thermal equilibrium. Cold plasma, also called nonthermal plasma, is particularly appropriate for textile surface modification and processing because most fiber-based materials are heat-sensitive polymers. Cold plasma treatments can be used to improve the fiber-matrix adhesion by introducing polar groups, by deposition of a new layer of the same polymer or by changing the surface roughness and chemistry of the substrate. Such forms of treatments have also the major advantage of inducing significant surface chemical and morphological modifications improving hydrophilicity and making fibers more accessible to various chemical specie, including dyes, without altering the bulk properties of the materials. Cold plasmas may be divided into atmospheric pressure plasmas and vacuum or low-pressure plasmas. Low-pressure plasma remains the preferred technology to achieve various effects by etching, polymerization or formation of free radicals on the surface of the textile substrate as in the case of superhydrophobic and flame-retardant coatings. Moreover, in the case of polyester and polypropylene fabrics, dyeing the low-pressure plasma technologies showed the best results. However, it is clear from the literature analysis that in the last years, atmospheric plasma technologies have been effectively employed as a suitable alternative and cost-competitive method to low-pressure plasma and wet chemical treatments, avoiding the need of expensive vacuum equipment and allowing continuous and uniform processing of fibers surfaces.